Brussels: livestock identification - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Following the recent outbreaks of livestock diseases in Europe, the identification and registration of individual animals has become an essential element of the EU´s livestock management programme.